Pembelajaran Menyimak Berbasis Pendidikan Karakter - Jelita Dwi Septya; Adinda Widyaningsih; Isma Nur Khofifah Br. BB; Sri Herdianti Harahap (Universitas Dehasen Bengkulu, 2022)
Listening based on character education is a way of listening that has a type of language skill that requires awareness. Listening is also an active receptive language skill. In listening activities, one must activate his mind to be able to identify the sounds of language, understand them, and interpret their meanings so that the message conveyed by the speaker is clearly captured. Listening based on character education can also shape the character of students when listening or paying attention to the interlocutor saying something to him.